2016
DOI: 10.4236/ojo.2016.612049
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Traumatic Complex Acetabulum Fractures with Open Reduction and Internal Fixation: 200 Cases

Abstract: Objective: Acetabular fractures are common injuries in Iran. We assess the functional outcome of open reduction and internal fixation management of displaced Complex acetabular fractures. Materials and Methods: We analyzed a case series of patients with open reduction and internal fixation (ORIF) for complex acetabular fractures. Two hundred patients (132 men, 68 women) in four age groups including with a mean age of 43.39 ± 6.18 years (range 20 -59 years) and a mean follow-up of 82.34 ± 12.48 months (range 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Our study results showing excellent functional outcome in 50% of patients, is similar to a previous study of 200 patients with complex acetabular fractures (74.6%) 12 and a meta-analysis of 16 studies (50.3%). A comparative analysis of the functional results of acetabular fractures treated with internal fixation in this study showed comparable results to the meta-analysis by Giannoudis, et al using the Harris hip score and the Merle d aubigne score with a p-value of 0.6281 and 0.3734 respectively (Table 8).…”
Section: Discussionsupporting
confidence: 91%
“…Our study results showing excellent functional outcome in 50% of patients, is similar to a previous study of 200 patients with complex acetabular fractures (74.6%) 12 and a meta-analysis of 16 studies (50.3%). A comparative analysis of the functional results of acetabular fractures treated with internal fixation in this study showed comparable results to the meta-analysis by Giannoudis, et al using the Harris hip score and the Merle d aubigne score with a p-value of 0.6281 and 0.3734 respectively (Table 8).…”
Section: Discussionsupporting
confidence: 91%
“…A number of studies have focused on the biomechanical consequences of acetabular fracture [28][29][30][31][32]. These studies can be divided into those focusing on.…”
Section: Biomechanical Consequences Of Acetabular Fracturementioning
confidence: 99%
“…Several studies have focused on the alteration of contact area and stresses in the joint as a result of the fracture [28][29][30][31][32]. All fracture patterns showed a change from a uniform contact pattern to one of increased contact area and peak pressures in the superior acetabulum.…”
Section: Intra-articular Contact Characteristicsmentioning
confidence: 99%
“…Men sustain about 75% of all pelvic injuries. With obese patients, the risk of blunt trauma-related pelvic fracture rises 3 .…”
Section: Introductionmentioning
confidence: 99%